Bimodal dynamics of viscous pearls - Auriane Huyghues Despointes; Abhijit Kumar Kushwaha; Jérôme Fresnais; Tadd Truscott; David Quéré (Proceedings of the National Academy of Sciences, 2026)
Droplets on super-repellent materials adopt the shape of pearls, which makes them highly mobile, owing to the conjunction of low contact line pinning with small dynamical friction. This property is especially valuable when drops are viscous, a case where we expect super-repellency to minimize the friction associated with viscosity. Here, we report that viscous droplets on highly repellent inclines can have two modes of descent, depending on the way they are deposited: either they run at the fast speed expected for pearls or they are 30 to 60 times quicker, which defines a super-fast regime of motion. We show that this effect relies on the tenuousness of the contact with the substrate. Consequently, this contact can be dynamically “erased” by the insertion of a cushion of air, which makes droplets glide at a speed both high and independent of their viscosity. We characterize these lubricating films (thickness and onset of appearance) and finally show that super-fast pearls initiated on a superhydrophobic (SH) surface can maintain their velocity and shape even on a hydrophilic solid.